36-(9-2m)7m=(m-9)

Simple and best practice solution for 36-(9-2m)7m=(m-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-(9-2m)7m=(m-9) equation:



36-(9-2m)7m=(m-9)
We move all terms to the left:
36-(9-2m)7m-((m-9))=0
We add all the numbers together, and all the variables
-(-2m+9)7m-((m-9))+36=0
We multiply parentheses
14m^2-63m-((m-9))+36=0
We calculate terms in parentheses: -((m-9)), so:
(m-9)
We get rid of parentheses
m-9
Back to the equation:
-(m-9)
We get rid of parentheses
14m^2-63m-m+9+36=0
We add all the numbers together, and all the variables
14m^2-64m+45=0
a = 14; b = -64; c = +45;
Δ = b2-4ac
Δ = -642-4·14·45
Δ = 1576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1576}=\sqrt{4*394}=\sqrt{4}*\sqrt{394}=2\sqrt{394}$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-64)-2\sqrt{394}}{2*14}=\frac{64-2\sqrt{394}}{28} $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-64)+2\sqrt{394}}{2*14}=\frac{64+2\sqrt{394}}{28} $

See similar equations:

| 2x-75=75 | | 1=0.2x-0.9-20 | | 9+32=-5(5x-8) | | 3a=5(2a+7) | | 4x+30=102 | | 33.374=-4.51x | | 6x+5-5x=15-27 | | 1=0.2x-0.9x-48 | | 4d​ −9=−3 | | (6x+14)+(3x+29)=0 | | 1/2(4x+10)=19-x | | (2x-50)+(7x)=180 | | -8(a-4+3a=2(4a+9)+1 | | 9+7x=9+7x | | 4d−9=−3 | | 9+7x=7x-9 | | 24+4.50x=200/x-1 | | 5n/2-3n=3/4 | | 81=1/2x(9) | | -6+(x/4)=5 | | 3.7+10m=8.54 | | 0.3x+15=2004 | | 7(p+3)-1=5(p+4)+2p | | 6=8v+2(3-4v) | | 4t=7(2t+2) | | 4(x=2)-8=20 | | 15000+160y=24000-200y | | 21=8x+1-4 | | 1/3(6x-9)=-3 | | 3b-3b+2=14 | | m/3-2=7 | | -30=8+x |

Equations solver categories